1988
DOI: 10.1128/mcb.8.3.1275-1281.1988
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Encoding the Major Beta Tubulin of the Mitotic Spindle in Physarum polycephalum Plasmodia

Abstract: The multinucleate plasmodium of Physarum polycephalum is unusual among eucaryotic cells in that it uses tubulins only in mitotic-spindle microtubules; cytoskeletal, flagellar, and centriolar microtubules are absent in this cell type. We have identified a beta-tubulin cDNA clone, beta 105, which is shown to correspond to the transcript of the betC beta-tubulin locus and to encode beta 2 tubulin, the beta tubulin expressed specifically in the plasmodium and used exclusively in the mitotic spindle. Physarum amoeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…For example, certain tubulins and one kinesin – major components of the spindle assembly pathway – are differentially expressed between the plasmodium and amoebae ( Figure 4G ). We find that alpha tubulin 1a (TBAD) and beta tubulin 1 (TBB1) are spindle markers expressed in both states, whereas alpha tubulin 1b (TBAN) and beta tubulin 2 and 4 (TBB2, TBB4) are only detected at high levels in the plasmodium, consistent with previous reports ( Burland et al, 1988 ; Burland et al, 1983 ). Also, the epsilon and gamma tubulin chains (TBE, TBG) involved in centrosome duplication and spindle formation and the spindle-associated kinesin KIF1 are detected at much higher levels in the plasmodium.…”
Section: Resultssupporting
confidence: 92%
“…For example, certain tubulins and one kinesin – major components of the spindle assembly pathway – are differentially expressed between the plasmodium and amoebae ( Figure 4G ). We find that alpha tubulin 1a (TBAD) and beta tubulin 1 (TBB1) are spindle markers expressed in both states, whereas alpha tubulin 1b (TBAN) and beta tubulin 2 and 4 (TBB2, TBB4) are only detected at high levels in the plasmodium, consistent with previous reports ( Burland et al, 1988 ; Burland et al, 1983 ). Also, the epsilon and gamma tubulin chains (TBE, TBG) involved in centrosome duplication and spindle formation and the spindle-associated kinesin KIF1 are detected at much higher levels in the plasmodium.…”
Section: Resultssupporting
confidence: 92%
“…Cells survive disruption of TUB3 but not TUB1 (Schatz et al, 1986b). Northern blots with either gene as probe suggested that TUB1 transcript was more prevalent than TUB3, although probe crosshybridization prevented accurate quantification (Schatz et al, Burland et al (1983), Burland et al (1984), Burland et al (1988); Schedl et al (1984b), Krämmer et al (1985); Singhofer-Wowra et al (1986), Monteiro and Cox (1987a), Monteiro and Cox (1987b), Green et al (1987) 1986a). The idea that cells harbor more Tub1 than Tub3 subunits is consistent with the finding that although lethal, tub1Δ can be rescued by increased expression of TUB3 (Schatz et al, 1986b).…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…Chlamydomonas reinhardtii tua1, tua2 tub1, tub2 each isoform: differential anti-tubulin drug resistance Kato- Minoura et al (2020). Physarum polycephalum altA, altB(N), altB(E), betA, betB, betC altA, altB(N), altB(E): MT assembly in plasmodia and myxamoeba Burland et al (1983), Roobol et al (1984), Cunningham et al (1993);Gerber et al (2022), altA builds flagellar MTs via PTM in amoeba and flagellates Green and Dove (1984), Blindt et al (1986), Diggins and Dove (1987), Sasse et al (1987); betA: MT structure assembly during myxamoeba stage Burland et al (1988), Diggins-Gilicinski et al (1989), Gerber et al (2022; betB: constitutively expressed in plasmodia and myxamoeba Werenskiold et al (1988), Paul et al (1989), benzimidazole resistance to both plasmodia and myxamoeba Burland et al (1984); betC: anastral mitotic spindle assembly in plasmodia Burland et al (1983), Roobol et al (1984), Gerber et al (2022), MT assembly in developing cells during amoeboid-plasmodial transition Solnica-Krezel et al (1988). *In Table 2, gene names are presented using organism-specific syntax.…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
See 2 more Smart Citations